Amalan taktik sosialisasi pengetua baru: Satu kajian kes di Pulau Pinang - Norashimah Ismail,; Jamaliah Abdul Hamid,; Foo, Say Fooi; Suhaida Abdul Kadir, (penerbit ukm, 2009)
This qualitative case study is intended to examine the socialization tactics of new principals in national secondary schools in Penang. The sujects were chosen using the purposive sampling method. Eight new principal participants were interviewed, each having about three years experience in their appointment. Data were collected using the semi-structured interview method. Data triangulation were compiled by interviewing several teachers at the new principal’s school. The findings of the study exhibited very few socialization tactics were implemented by higher authorities to assist new principals socialisation in Malaysia. Infact new principals are forced to undergo their own socialisation tactics to familiarise with culture, norms and organisational system of school.